The founders the origins of the ANC and the struggle for democracy in South Africa - Odendaal, Andre (Auckland Park Jacana Media, 2012)
The African National Congress was founded a hundred years ago, in january 1912. But the roots of the ANC run deeper in South African history. For fifty years before it was formed, a remarkable group of African Intellectuals, activists and organisations prepared the way by standing up for African rights in the new colonial world. Their story has been painstakingly recovered by Andre Odendaal, who has pieced togehter their astonishing achievements and the broad, inclusive vision they proposed for the future. Without knowing their story, one cannot properly understand South Africa today, or the immense legacy they left with their deep-rooted tradition of African Constitutionalism.
Includes bibliographical references Index
Keywords: African National Congress-History. National liberation movements-South Africa. South Africa-History. South Africa-Politics and government -20th century.Tales-Africa. Folklore-Africa